Using a signal detection approach to understand the impacts of processing fluency and efficacy on accuracy in misinformation detection - Fort, Kara S.; Shulman, Hillary C. (Frontiers in Psychology, 2024)
This experiment (N = 1,019) examined how a state of processing fluency, induced through either an easy or difficult task (reading a simple vs. complex message or recalling few vs. many examples) impacted participants’ ability to subsequently detect misinformation. The results revealed that, as intended, easier tasks led to higher reports of processing fluency. In turn, increased processing fluency was positively associated with internal efficacy. Finally, internal efficacy was positively related to misinformation detection using a signal detection task. This work suggests that feelings of ease while processing information can promote confidence and a more discerning style of information processing. Given the proliferation of misinformation online, an understanding of how metacognitions – like processing fluency – can disrupt the tacit acceptance of information carries important democratic and normative implications.